Sebuah Galatia 3:28 dan Pelayanan Perempuan: Sebuah Penafsiran Menggunakan Epistolary Approach Untuk Menjelaskan Pelayanan Kaum Perempuan di Gereja - Christo Antusias Davarto Siahaan (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2024)
Galatians 3:28 is one of the Biblical texts that supports equality between women and men. However, this verse is not widely used to provide an understanding of opportunities for women to serve in the church. Therefore, by using the Epistolary Approach, an understanding based on Galatians 3:28 regarding women's service opportunities in the church can be obtained. This understanding is first that Galatians 3:28 provides a positive attitude towards women's ministry in the church, namely that Galatians 3:28 supports women's ministry, because women's ministry is one of the implications and results of the true Gospel delivered by the apostles of the Lord Jesus Christ. Then secondly, Galatians 3:28 gives a positive impression of women's opportunities to serve the church as something that is expected.